Exposure Analysis of Heavy Metals in Dugs Well Water of Telutu Jaya Village Community, Tinanggae District, South Konawe Regency - Firdaus, Firdaus; Ambarsari, Ika Sartika; Anshari, Erwin; Wahab, Wahab; Saputra, Irfan (Universitas Ibn Khaldun Bogor, 2024)
The ideal drinking water requirement is clean water that is colorless, odorless, and tasteless, doe not contain pathogenic germs, does not contain chemicals or heavy metals, does not endanger the health of living things, and is not economically harmful. The ARKL study is intended to calculate or predict the risk to human health, including identification of the presence of uncertainty factors, tracing to specific exposures, taking into account the inherent characteristics of the agent of concern, and the characteristics of specific targets. Based on the ARKL study, the minimum RQ and maximum RQ values for each risk agent are <1 (safe). This study used dug-well water from the community of Telugu Jaya Village. The purpose of the study was to assess the risk of exposure to heavy metals contained in dug-well water. Measurement parameters were carried out in the form of Ph, TSS, and nine heavy metal elements (Cu, Cd, Cr6+, CrT, Pb, Ni, Fe, Zn, and Co). After the measurement, the risk of heavy metal exposure to local community-dug well water was analyzed. The results showed that HI <1, so it was concluded that the level of heavy metal intake from the dug well was still below the reference dose (RfD), which means that the exposure limit was still safe.